Comparing fiscal federalism - Palermo, Francesco; Valdesalici, A. (Alice) (Studies in territorial and cultural diversity governance, 2018)
Comparing Fiscal Federalism investigates intergovernmental financial relations and the current de jure and de facto allocation of financial and fiscal powers in compound states from a comparative and interdisciplinary perspective. The volume combines theoretical approaches with case studies and involves scholars from various disciplines, in order to provide a comprehensive analysis of different approaches, developments and trends. This includes outlining fiscal federalism's basic principles and overall frameworks, investigating current constitutional/legislative settings and how financial systems function, as well as zooming in on a selection of emerging issues in financial and fiscal relations. The single chapters are based on comparative investigations under the umbrella of a broad definition of fiscal federalism that includes all varieties of federal systems.